Short‐term effects of NTI‐tss and Michigan splint on nocturnal jaw muscle activity: A pilot study. Issue 3 (25th December 2020) - Lukic, Nenad; Saxer, Timo; Hou, Mei‐Yin; Zumbrunn Wojczyńska, Aleksandra; Gallo, Luigi M.; Colombo, Vera
Abstract: Objectives: Sleep bruxism is mostly assessed by reporting of tooth‐grinding or clenching during sleep and by clinical signs (tooth wear, cracks, or fractures). Parafunctional tooth damage is usually prevented by employing occlusal appliances mainly of the full arch covering type (Michigan splint) and of the partial type covering only central incisors (NTI‐tss). To date, the effects of occlusal appliances on sleep bruxism or jaw muscle activity during sleep are still controversial. The present study is a randomized controlled clinical trial that evaluated the effects of two different splint designs on jaw muscle activity in sleep bruxers otherwise healthy. Material and Methods: Ten patients from a private dental practice were treated by a single operator. A Michigan splint and an NTI‐tss device were manufactured individually and used at random order. Electromyographic jaw muscle activity was recorded for four consecutive nights in the first, fourth, and seventh week with and without splint. Participants reported on splint comfort and side effects. Results: Muscle activity decreased only while wearing the NTI‐tss device. Most patients preferred though the Michigan splint due to its greater wearing comfort. Conclusions: NTI‐tss devices proved more effective for the reduction of jaw muscle activity during sleep. The main advantage of the prefabricated NTI‐tss is its prompt availability in an acute phase of temporomandibular disorders associated with sleep bruxism. In long‐term therapies, patients should be informed of the possible risk of irreversible occlusal changes. Subjective preferences, wearing comfort, and costs should also be considered.